Review of Strategies for Curbing Traffic Congestion in Sub-Saharan Africa Cities: Technical and Policy Perspectives - Rwakarehe, Eradius Edward (Tanzania Journal of Engineering and Technology, 2022)
This paper summarizes the causes of traffic congestion in sub-Saharan Africa (SSA) cities and the solutions to be adopted. According to the literature, the modal share for private cars, public transport (minibus and taxis); and walking & cycling are 8%, 34% and 40% respectively. From these figures, it has been found that although the private car mode is still used relatively little (as compared to developed countries); contrary to the expectation, traffic congestion in SSA cities is worse compared to cities of developed countries. This implies that, traffic congestion problem in SSA cities is largely associated with limited availability of road infrastructure. As opposed to traffic congestion solutions to most of the cities in developed countries, road expansion is still one of the major solutions towards solving the same problem in SSA cities. However, the issue remains as to how many lane-kilometers should be added to reach the optimal level. It is clear that we cannot keep expanding roads without a limit; therefore, transportation experts and land-use planners need to establish the benchmarks that will serve as limiting indicators. Apart from relatively poor land-use planning and inadequacy of road infrastructure, it has also been found that disorganized and informal public transport is another major cause of traffic congestion in SSA cities. Key words: Traffic Congestion, Public Transport, Car Ownership and Usage.